Wireless Volume Corrector for Natural Gas Flow Metering Using ESP32 Microcontroller and Open-Source Web Server - Handaja, Suka; Dewi, Astrie Kusuma; Triyanto, Roni Heru (JOIV : International Journal on Informatics Visualization, 2024)
The measurement of gas flow in energy transactions from an energy-producing company to an energy user is essential to evaluate, considering that measurement errors can accumulate, and losses can occur, which will be ongoing. The gas measurement process begins with measuring pressure and temperature parameters and the gas flow volume transacted. Then, the measured gas volume will be converted into a standard volume as the basis for gas buying and selling transactions (custody). This article conveys that a wireless volume corrector has been designed using the ESP32 microcontroller with Wi-Fi communication that can be integrated with the internet to support automatic meter reading systems. The measured data is collected in a database server using XAMPP, an open-system web server. Data stored on the database server is displayed via a web browser with a display of the last 5 data entered the web server. The web browser display is refreshed every second so that the display on the web browser is a live or online display. This research resulted in temperature, pressure, actual flow, and volume standard measurements with an error below 0.1%, which met the metrology requirements, instilling confidence in the system's reliability. This research proves that realizing a volume corrector with IoT technology can be done cheaply.